2017
DOI: 10.1038/s41598-017-01024-8
|View full text |Cite|
|
Sign up to set email alerts
|

Multidisciplinary study of the secondary immune response in grandparents re-exposed to chickenpox

Abstract: Re-exposure to chickenpox may boost varicella-zoster virus (VZV) immunity in the elderly. This secondary immune response is hypothesized to confer protection against herpes zoster. We longitudinally sampled 36 adults over the course of one year after re-exposure to chickenpox. The resulting 183 samples and those of 14 controls were assessed for VZV-specific T-cell immunity and antibody titres. The percentages of VZV-specific CD4+ IL-2-producing T-cells were increased in re-exposed grandparents compared to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…This is also in line with the original supervised approach where trimers were used which were statistically overrepresented in a TCR data set targeting a specific epitope or antigen, versus one that did not (Glanville et al, 2017). The weighting scheme was based on the combined CD8+ TCR repertoires of all the data collected within the study of (Ogunjimi et al, 2017). These were full repertoires without any prefiltering on epitope preferences and can therefore be considered as representing the modal TCR diversity.…”
Section: Distance Measuresmentioning
confidence: 82%
“…This is also in line with the original supervised approach where trimers were used which were statistically overrepresented in a TCR data set targeting a specific epitope or antigen, versus one that did not (Glanville et al, 2017). The weighting scheme was based on the combined CD8+ TCR repertoires of all the data collected within the study of (Ogunjimi et al, 2017). These were full repertoires without any prefiltering on epitope preferences and can therefore be considered as representing the modal TCR diversity.…”
Section: Distance Measuresmentioning
confidence: 82%
“…A number of other CEE countries endorse vaccination only for susceptible (medical or occupational) at-risk groups [1]. Barriers adoption of a UVV program among children include the public perception of varicella as a generally mild disease, cost, the risk of an increase in herpes-zoster incidence among those not vaccinated against varicella or herpes zoster predicted in multidisciplinary studies [10][11][12][13][14], and a temporary increase in herpes zoster cases following reduced circulation of varicella zoster virus under the influence of a UVV program ('exogenous boosting' hypothesis) [7,15,16]. The lack of availability of a registered varicella vaccine within some CEE countries -Bulgaria, for examplecan also act as a barrier.…”
Section: Introductionmentioning
confidence: 99%
“…21,47,56 This is likely because, these DoB were significantly lower than previous models but are consistent with immunological assays used to measure the duration of boosting in grandparents as described in the study above. 54 Furthermore, the rate of boosting in our model was driven within an age-and distance-based transmission network rather than a random-mixing network, potentially limiting contacts that could produce a boost, which is supported by the fact that our average number of boosts per person was low at 1.83.…”
Section: Discussionmentioning
confidence: 76%
“…6 A recent study showed that only 17-25% of grandparents who were exposed to chickenpox received a significant boost in VZV-specific immunity and that this boost typically lasted less than a year. 54 Using our agent-based model, we varied these unknown boosting parameters (e.g., DoB, WoI, degree and probability of boosting on contact) to see how those variations impacted the outcomes of chickenpox vaccination. By varying DoB and WoI simultaneously, we identified several boosting of immunity scenarios that could fit current Alberta data.…”
Section: Discussionmentioning
confidence: 99%